After-Hours and Weekend Phone Calls by Urological Subspecialty at a Tertiary Care Institution. Issue 2 (4th March 2021) - Golan, Ron; Haas, Christopher; Shah, Ojas
Abstract: Introduction: Many urology practices offer after-hours answering services through which patients or outside providers may access an on-call provider. These lines of communication are often unfiltered, allowing for a combination of urgent and non-urgent matters to reach the provider. The objective of this study was to evaluate the nature and frequency of after-hours phone calls among urological subspecialties. Methods: Phone calls occurring after-hours during the week (5 pm–7:59 am), weekends, and federal holidays were captured over 2019. The patient's provider and reason for calling were captured. The adult subspecialties included were endourology, oncology, reconstructive urology, female urology/voiding dysfunction, andrology/sexual medicine, and multispecialty/general. The reason for calling was categorized as either urgent/non-avoidable or non-urgent/avoidable, and the volume of after-hours and overnight calls was compared amongst subspecialties using the number of calls per 100 unique patients. Results: There were 2, 224 after-hours calls over the 1-year period; 48% of telephone calls were regarding urgent matters, while the remainder were non-urgent or potentially avoidable. Reconstructive and endourology had the highest number of after-hours calls (34.8 calls and 17.3 calls per 100 patients, respectively). Reconstructive received the most urgent overnight phone calls at 3 calls per 100 patients, followed by oncology (1.55 per 100 patients) and endourology (1.35 per 100 patients). Conclusions: Each urological subspecialty has varying acuity, which may influence the number of after-hours calls. Providers and their staff should optimize their work flow through triaging, counseling, and education in order to reduce the number of non-urgent after-hours calls.